Bolustherapy in the general chart of renewal of the lost functions of lower extremities for patients after the diaphyseal fracture of bones of shins - Zhelezniy A.D (Kharkov National Pedagogical University, 2010)
The results of the use of medical clay are considered as a physical therapy mean in the general chart of physical rehabilitation of patients. The existent methods of treatment clay are adapted for the physical rehabilitation of patients. Considered chemical components of local clays. Presented recommendation to the use of clay with the dosage of procedures during the physical rehabilitation of patients. As a result of application of author method for patients on 1-3 weeks the terms of physical rehabilitation grew short.